Enhanced n-hexane hydroisomerization over bicontinuous lamellar silica mordenite supported platinum (Pt/HM@KCC-1) catalyst. (17th July 2020) - Ibrahim, M.; Jalil, A.A.; Khusnun, N.F.; Fatah, N.A.A.; Hamid, M.Y.S.; Gambo, Y.; Abdulrasheed, A.A.; Hassan, N.S.
Abstract: A bicontinuous lamellar silica mordenite (HM@KCC-1) has been successfully synthesized by microemulsion technique assisted with mordenite-seed recrystallization, followed by protonation and impregnation with platinum (Pt). The catalysts were extensively characterized by XRD, N2 adsorption, FTIR, FESEM, TEM and ESR and the activity was tested in hydroisomerization of n -hexane. Fourier Transform-Infrared Spectroscopy (FT-IR) study through pyridine and 2, 6- dimethylpyridine adsorption revealed that Pt/HM@KCC-1 possessed abundant Lewis acid sites and moderate Brønsted acid sites while Pt/HM possessed strong Lewis and Brønsted acid sites. At 300 °C, the conversion of n -hexane on Pt//HM@KCC-1 reached 75% with 98% isomer selectivity and 74% isomer yield. The enhancement of catalytic performance is attributed to the well-dispersed Pt nanoparticles, tuned acidic properties and improved textural properties which provided a well balance in the acid/metal functions. Thus, favours the reaction towards higher hydroisomerization selectivity, limiting the undesired consecutive cracking reaction. Graphical abstract: Image 1 Highlights: HM@KCC-1 was synthesized via a microemulsion mordenite seed-crystallization system. HM@KCC-1 possessed high surface area with bicontinuous lamellar silica (KCC-1) morphology. Moderate Brønsted acid sites on Pt/HM@KCC-1 favoured hydroisomerization. Pt/HM@KCC-1 showed good Pt dispersion and no diffusional limitation. Pt/HM@KCC-1 gave the highest isomer yield of 74% at 300 °C.